Growth, nutrient acquisition and physiological responses of papaya (Carica papaya) plants to controlled low temperature stress - PRADHAN, SATYABRATA; GOSWAMI, A K; SINGH, S K; PRAKASH, JAI; GOSWAMI, SUNEHA; VISWANATHAN, CHINNUSAMY; TALUKDAR, AKSHAY; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2018)
Study of physiological response of different papaya (Carica papaya L.) genotypes to low temperature stress is of paramount importance owing to its higher susceptibility.The present study was conducted under controlled conditions of National Phytotron Facility, ICAR-IARI, New Delhi to investigate the effect of different low temperature regimes on growth, nutrient acquisition and other physiological parameters in five papaya genotypes and one distant relative, i.e. genus Vasconcellea cundinamarcensis known for cold tolerance. Results revealed that there was higher reduction in photosynthesis rate, stomatal conductance and transpiration rate under all the low temperature regimes, which leads to reduction of plant growth related parameters. Temperature treated plants showed 57.96% reduction in photosynthetic rate as compared to the control. Amongst the five genotypes, the lowest stomatal conductance was exhibited by V. cundinamarcensis (0.026 mol/m2/s) followed by P-9-5 (0.055 mol/m2/s). The lowest transpiration rate was also exhibited by V. cundinamarcensis (0.39 mol/m2/s) followed by P-7-9 (0.73 mol/m2/s). The highest per cent increase in the leaf potassium (K) was observed in genotype V. cundinamarcensis (49.15%), followed by P-7-9 (13.29%) while for roots, it was in P-7-9 (128.81%). The genotype V. cundinamarcensis also showed the highest mean calcium (Ca) accumulation in both leaf (3.58%) and root (3.67%). Low temperature treatment, in most of the cases, significantly affected the leaf and root nutrient contents, although the level of change was nutrient and genotype specific.